Characterization and genetic diversity of Phytophthora palmivora from cocoa in Malaysia and its biological control using endophytic bacteria - Alsultan, Wael M. K. (2019)
Black pod disease of cocoa, caused by Phytophthora palmivora, is a serious problem to cocoa growers in Malaysia and worldwide. There are a few research efforts have been conducted to study the causal agent of black pod disease of cocoa in Malaysia. At present, there are no reports available on the determination of genetic diversity among P. palmivora populations in cocoa growing areas of Malaysia. Therefore, this study was initiated to isolate and identify Phytophthora species from main cocoa plantations infected by black pod disease in Malaysia using sequence analyses of the ITS rDNA, cytochrome c oxidase subunit 1, and translation elongation factor 1α regions. This study was also examined the genetic diversity within 56 P. palmivora isolates obtained from the different host, geographical regions and years in Malaysia using Inter-simple sequence repeat (ISSR) and random amplified polymorphic DNA (RAPD) markers. In addition, this study was carried out to isolate, characterize and screen bacterial endophytes from cocoa plants for their biological control activities. Their mechanisms of action as well as the ability to reduce black pod rot disease were also investigated. A total of 36 Phytophthora isolates were obtained from different infected cocoa plantations from five states of Malaysia. Six Phytophthora isolates obtained from durian and available at the Department of Plant Protection, Universiti Putra Malaysia were also used in this study. Results of phylogenetic analyses of individual and combined dataset of the ITS rDNA, COX I and EF-1α confirmed that all Phytophthora isolates belonged to P. palmivora. The results also confirmed that the three examined regions could differentiate P. palmivora at the species level. P. palmivora isolates obtained from cocoa and durian were clustered into different subclades based on the three regions examined. The results of both markers indicated relatively high diversity among P. palmivora isolates. The complete separation was based on host and year of isolation. In total, 100 endophytic bacterial isolates were obtained from healthy cocoa tissues (leaves, branches and fruits) from seven states of Malaysia. The isolated bacteria were screened by dual culture assay and culture filtrate test for their antagonistic properties towards P. palmivora in vitro. The best two isolates Pseudomonas aeruginosa (AS1) and Chryseobacterium proteolyticum (AS2) with more than 80% inhibition of radial growth (PIRG) were selected for subsequent experiments. Bioactive volatile compounds from ethyl acetate crude extract were identified using gas chromatography-mass spectrometry (GC). The effectiveness of Pseudomonas aeruginosa and Chryseobacterium proteolyticum isolates in reducing black pod lesion was confirmed on detached cocoa pods. These results confirmed that these two bacterial isolates have potential to be used as bio-control agents against P. palmivora.